Strategi Dakwah Ustadz Muksin Ariyanto Melalui Pengajian Al-Qur’an Di Masjid Nurul Iman Desa Babat Lama Kabupaten Lahat Sumatera Selatan - Andre Febrianto; Abdur Razzaq; Mohd. Aji Isnaini (CV. ITTC INDONESIA, 2023)
This thesis is entitled Ustadz Muksin Ariyanto's Da'wah Strategy Through Al-Qur'an Recitation at the Nurul Iman Mosque, Babat Lama Village, District. East Kikim, Lahat Regency, South Sumatra. The aim of this research is to find out the da'wah strategy used by Ustadz Muksin Ariyanto in the Al-Qur'an recitation congregation in Babat Lama Village and to find out what are the supporting and inhibiting factors of Ustadz Muksin Ariyanto's da'wah strategy in Al-Qur'an recitation in Babat Village. Long. The research method used in this thesis is a qualitative method, the researcher used the informant Ustad Muksin Ariyanto. Data collection in this research used interviews, observation, documentation and data analysis techniques used in this research, namely data reduction, data presentation and drawing conclusions. The results obtained from this research, first is al-manhaj al-athifi or Sentimental Da'wah Strategy. This strategy focuses more on the heart aspect and moves the feelings and inner thoughts of the preaching partner or mad'u. Giving a da'wah partner impressive advice, calling with gentleness, or providing satisfactory service. It's the same thing when Ustadz Muksin delivers his preaching material to the congregation in a gentle way and embraces them and then gives good advice to encourage them to be enthusiastic in study religious knowledge. Supporting factors in Ustadz Muksin Ariyanto's preaching include support from the village government by participating directly in recitation activities and providing operational funds for recitation activities and a sense of family and solidarity between fellow reciters. What is an inhibiting factor in Ustadz Muksin Ariyanto's preaching is that there are still many environmental influences around recitation activities or activities outside of recitation such as very loud music, lack of public awareness in understanding and practicing the teachings of the Islamic religion because it has not yet become a culture in society regarding its importance. to study religious knowledge.